The effect of financial literacy, financial experience, financial self-efficacy on consumption behavior with financial technology as a mediating variable in the millennial generation - Girsang, Febrina Jayanti; Purnama, Eka Desy (Goodwood Publishing, 2025)
Purpose: This study aims to examine the influence of financial literacy, financial experience, and financial self-efficacy on consumption behavior with financial technology as a mediating variable in the millennial generation. Research Methodology: A quantitative approach was applied using purposive sampling of 200 active e-commerce users aged 29–44 years with prior FinTech experience. Data were collected through online questionnaires and analyzed using the WarpPLS structural equation modeling. Validity, reliability, and hypothesis testing were conducted using SmartPLS 3.0. Results: The findings show that financial literacy, financial experience, and financial self-efficacy each have a significant positive effect on consumption behavior. Financial self-efficacy had the strongest direct effect. Mediation testing revealed that FinTech significantly mediated the relationship between financial self-efficacy and consumption behavior, but did not significantly mediate financial literacy or financial experience. The model explains 77% of the variance in consumption behavior and 72% through fintech mediation. Conclusions: Millennials’ financial behavior is mainly driven by self-efficacy, with fintech enhancing this effect, while its role in mediating financial literacy and experience remains limited. Limitations: The study is restricted to millennials in Indonesia and e-commerce contexts, with cross-sectional data that limit causal inference Contribution: This study highlights financial self-efficacy as the main driver of responsible consumption in the fintech era and provides insights into designing programs that combine literacy, experience, and confidence building.